ANALISIS FAKTOR PENERIMAAN TEKNOLOGI DALAM PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR SISWA SEKOLAH DASAR - Elistya Rimawati; Ari Wibowo (Universitas Muhammadiyah Semarang, 2018)
The Industrial Revolution 4.0 is characterized by digitalization and automation. Internet technology is one of the fastest growing literacy. This also affects the world of education, a change in learning strategies. The teacher is no longer the only source of learning, but acts as a facilitator. Many learning resources can be used in learning, one of which is the internet. Technology acceptance is used to model the behavior of elementary school teachers in choosing the Internet as a learning resource. The factors observed were the perception of Information Technology, Ease, and Risk. Research data was obtained by distributingquestionnaires randomly at elementary schools in Surakarta and surrounding areas. The data shows that the perception of Information Technology has the highest relationship value of 0.514 and the ease of perception has a value of 0.349 and risk perception has a relationship value of -0.341. Interest in elementary school teachers using the Internet is influenced by the efficiency and effectiveness of information technology. Perception Risk is not a barrier in using the internet as a learning resource for elementary school students. Keywords: Internet, Information Technology, Teacher's Interest